Efektivitas Kualitas Produk terhadap Keputusan Pembelian Konsumen: Literature Review Manajemen Pemasaran - Dewi Puspitasari; Muhammad Asir; Rahmi Rahmi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Quality products are the main key in winning market competition, which in turn will be able to provide higher satisfaction value to consumers. The purpose of this study was to see the effect of product quality on consumer purchasing decisions. The method in this article is a qualitative method with literature study or Library Research. The purpose of this article is to analyze existing theories by looking at their comparison with previous theories in the research literature. The literature used is literature from research results or reviews that are recorded in national and international scientific articles related to financial management. All articles used are sourced from the electronic literacy data search engine Mendeley and Google scholar. Based on the theory of several articles on the results and discussion, the conclusion in this article is that product quality has a positive effect on consumer purchasing decisions. Keywords: consumers, product quality, purchasing decisions,